TOURISM PROMOTION STRATEGY OF PUNCAK MAS BANDAR LAMPUNG CITY - Bangun Suharti; Agnesia Dian Karima; Iqbal Al Bifari (Metakom, 2020)
Puncak Mas is one of the leading tourist attractions in the city of Bandar Lampung. This can be seen from the enthusiasm of the community to come to visit Puncak Mas. The achievement of Puncak Mas in attracting public visits, was recorded at 6,000 to 7,000 on holiday weekends. This study is intended to find out how the promotion strategy carried out by the management of Puncak Mas. This study uses Muncak marine binoculars as a comparison. The data in this study were obtained by conducting interviews with the manager of Puncak Mas and a little with Muncak marine binoculars. Observations and documentation carried out for field verification. Visitors who were interviewed only to crosscheck data from interviews with managers. The results of this study found that the promotion strategy undertaken by Puncak mas was in accordance with the marketing mix concept, by combining 4 elements of P, namely product, price, place and promotions. Promotion using social media and digital media according to the demands of the times has been done by the management and owner (owner) of Puncak Mas.